Some synergims in the degradation of polypropylene geotextiles - J. R. Carneiro (2014)
Durability (resistance to degradation) is currently an important topic of research in geosynthetics. The existing studies about this topic consider mostly the isolated action of the degradation agents and do not account for the interactions that can occur between them. In contrast to previous studies, this work deals with some interactions that may exist between the degradation agents of the geosynthetics. For this purpose, a non-woven polypropylene geotextile was exposed to various degradation tests. First, the material was exposed in isolation (single exposure) to installation damage, abrasion, liquids (nitric acid and zinc (II) nitrate solutions), thermo-oxidation and artificial weathering. This allowed evaluating the isolated effect of these degradation agents. In a second phase, the geotextile was successively exposed to some combinations of two of the previous agents, in order to evaluate the occurrence of synergetic effects between them. Results showed that, in some cases, the combined action of two agents was different (more damaging) than the sum of the individual effects of both agents.